2023
DOI: 10.1364/oe.482464
|View full text |Cite
|
Sign up to set email alerts
|

Polaritonic coherent perfect absorption based on self-hybridization of a quasi-bound state in the continuum and exciton

Abstract: Enhancement of light-matter interactions is of great importance for many nanophotonic devices, and one way to achieve it is to feed energy perfectly to the strongly coupled system. Here, we propose gap-perturbed dimerized gratings based on bulk WS2 for flexible control of the strong coupling or self-hybridization of a quasi-bound state in the continuum (quasi-BIC) and exciton. The simulation results show that when a gap perturbation is introduced into the system resulting in the Brillouin zone folding, BIC tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The resonance wavelength of BIC is 1106 nm, and the near field distribution E y indicates that it concentrates around high-dielectric material rather than the air gap. When the perturbation δ is introduced, the BIC will transfer into quasi-BIC with finite quality factor Q and non-zero linewidth, and its formation mechanism could be attributed to the Brillouin zone folding [6]. The transmission spectra with varying perturbation δ are presented in Fig.…”
Section: Simulation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resonance wavelength of BIC is 1106 nm, and the near field distribution E y indicates that it concentrates around high-dielectric material rather than the air gap. When the perturbation δ is introduced, the BIC will transfer into quasi-BIC with finite quality factor Q and non-zero linewidth, and its formation mechanism could be attributed to the Brillouin zone folding [6]. The transmission spectra with varying perturbation δ are presented in Fig.…”
Section: Simulation and Discussionmentioning
confidence: 99%
“…In 1929, John von Neumann and Wigner introduced the concept of BIC as a solution to the single-particle Schrödinger equation in quantum mechanics [1]. BIC has been applied in various systems, such as fluid dynamics, acoustics, electromagnetic waves, and water waves [2][3][4][5][6][7][8][9][10][11]. Recently, photonic nanostructures have become a suitable platform for investigating the properties of BICs, paving the way for potential applications in low-loss lasers, sensors, and filters [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Besides using the TMDC monolayer over or inside the periodic structures [151156] , fabricating bulk TMDC materials to form metasurfaces can efficiently improve the spatial overlap of the cavity mode profile with the emitters to make more significant strength of light–matter interaction. While several theoretical bulk WS2 works give large Rabi splitting that even exceeds 200 meV [157161] , recent experiments show a tuned strong coupling system with maximum Rabi splitting of 116 meV by constructing BIC-driven metasurfaces composed of bulk WS2 [162] . Besides TMDC materials, perovskite metasurfaces are also worth trying to enhance the strength of light–matter interaction.…”
Section: Explored Effects Enabled By Bicsmentioning
confidence: 99%
“…For instance, in 2021, Zong et al achieved a Rabi splitting of 120 meV by strong coupling QBIC modes to excitons in a WS 2 bulk material [39]. In 2022, Gu et al increased the Rabi splitting to 235 meV using the similar scheme [40]. In 2023, Xie et al achieved a remarkable Rabi splitting of up to 464 meV, demonstrated that the self-hybridized BIC-X coupling strength in this 2D metasurface can be dramatically enhanced with the assistance of a Fabry-Pérot cavity, which represents the highest Rabi splitting value in current strong coupling studies [41].…”
Section: Introductionmentioning
confidence: 99%